Effects of elastic resistance training on lower extremity muscle strength, balance and functional mobility among institutionalized elderly in Malaysia - Motalebi, Seyedeh Ameneh (2015)
To provide and make accessible the benefits of the resistance exercises for older people, development of a low-cost and also useful alternative equipment are essential. So, this study examined the effects of a 12-week progressive elastic resistance training on lower-extremity muscle strength, static and dynamic balance and functional mobility of older adults residing in a governmental welfare home (Rumah Seri Kenangan), in Cheras, Selangor, Malaysia. Fifty one subjects were qualified to participate in this quasi-experimental designed study. They were allocated to either the 12-week progressive elastic resistance training (N= 26) or in the control group (N = 25). Forty-five of them (male = 26 and female = 19) with mean age 70.7 ± 6.6 years successfully completed the program. The majority of the subjects were Malay ethnicity (73.3%). The exercise group was trained twice per week, performing 1-3 sets of 8-10 repetitions for each of nine lower-extremities elastic resistance exercises. Exercises were performed in both sitting and standing positions at moderate intensity (5 or 6 of OMNI perceived exertion scale) using elastic bands in different resistances. The dependent variables consisted of lower extremity muscle strength [sit-to-stand test (STS)], dynamic balance [forward functional reach test (FFRT), lateral reach test (LRT) for right and left hands, four square step test (FSST), and step test for right and left leg], static balance performance [tandem stand Test (TST), one leg stand (OLS) test with the eyes opened and closed], functional mobility [timed- up-and-go (TUG) test and 6-minute walking Test (6MWT)] were measured before and after 6 and 12 weeks intervention. There were no significant differences in the distributions of all tests scores for the dependent variables between the exercise and control groups prior to the intervention. The post-intervention measurements showed significant improvements in lower-extremity muscle strength (22.60%, p < 0.001) and functional mobility (18.71% in TUG test and 12.09% in 6MWT, p < 0.001). There was also a significant increase in the dynamic balance ability by FFRT (18.51 %, P < 0.001), LRT for right hand (19.98%, p < 0.001) and for left hand (17.69%, p < 0.001), FSST (14.67%,p < 0.001), and step test for right leg (18.36%, p < 0.001) and for left leg (18.80%, p < 0.001). No significant improvements were observed in the static balance measured by tandem stand test (3.25%, p > 0.05), OLS with eyes opened (9.58%,p > 0.05) and with eyes closed (-0.61 %,p > 0.05). The findings support the feasibility and efficacy of a simple and inexpensive resistance training program for improving lower-extremity muscle strength, dynamic balance and mobility in the institutionalized older adults. This training can be considered as an effective public health strategy for improvement of daily acti vity performance and reducing the risk of falling in the growing older population.